2019
DOI: 10.15171/apb.2019.053
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative and Anti-metastatic Potential of Curcumin Analogue, Pentagamavunon-1 (PGV-1), Toward Highly Metastatic Breast Cancer Cells in Correlation with ROS Generation

Abstract: Purpose: Pentagamavunon-1 (PGV-1) is a curcumin analogue that shows cytotoxic activity in various cancer cells. In this study, we evaluated the effect of PGV-1 on a highly metastatic breast cancer cell line, the 4T1 cells, as an anti-metastatic and anti-proliferative agent. Methods: Cell viability was evaluated using MTT assay; while cell cycle profile, apoptosis incidence, and ROS intracellular level were determined by flow cytometry. Cell senescence was observed under senescence-associated-β-galactosidase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
40
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 27 publications
11
40
1
Order By: Relevance
“…Furthermore, curcumin analog of A501 and WZ35 induces G2/M cell cycle arrest in non-small lung cancer cells, and prostate cancer cells (Xia et al, 2014;Zhang et al, 2015) and EF24 also induce G2/M arrest in MAD-MB cell line by increasing level of ROS, while simultaneously decrease the cellular level of GSH (Adams et al 2005b). Results of this present study was supported by a previous study that demonstrated G2/M cell cycle arrest upon PGV-1 treatment ( 2 and 4 μM) in 4T1 cells (Meiyanto et al 2019). Moreover, the same author showed S phase arrest upon curcumin treatment in concentration of 25 μM in 4T1 cells.…”
Section: Curcumin and Its Analog Induce Cell Cycle Arrest On The 4t1 supporting
confidence: 90%
“…Furthermore, curcumin analog of A501 and WZ35 induces G2/M cell cycle arrest in non-small lung cancer cells, and prostate cancer cells (Xia et al, 2014;Zhang et al, 2015) and EF24 also induce G2/M arrest in MAD-MB cell line by increasing level of ROS, while simultaneously decrease the cellular level of GSH (Adams et al 2005b). Results of this present study was supported by a previous study that demonstrated G2/M cell cycle arrest upon PGV-1 treatment ( 2 and 4 μM) in 4T1 cells (Meiyanto et al 2019). Moreover, the same author showed S phase arrest upon curcumin treatment in concentration of 25 μM in 4T1 cells.…”
Section: Curcumin and Its Analog Induce Cell Cycle Arrest On The 4t1 supporting
confidence: 90%
“…Santel and colleagues [ 45 ] found that specific GLO1 activity in curcumin-treated JIMT-1 breast carcinoma cells was lower than in non-treated cells, decreasing dose-dependently. In addition, Meiyanto et al [ 46 ] reported that curcumin finely binds to GLO1 and induces autophagy in 4T1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, several curcumin nanoformulations have been prepared to provide shielding to curcumin from hydrolysis and to increase its retention period in the body [ 93 ]. There exist few curcumin-based nanoformulations with more significant pharmaceutical potential in diagnosing various human diseases [ 94 ], a number of studies have shed light on their anti-proliferative potential [ 95 , 96 ], but only a scarce amount of them have searched for the therapeutic effects of curcumin nanoformulations in PC [ 97 ]. So, here, we have summarized the curcumin nanoformulations and their significance in regulating PC cell growth.…”
Section: Curcumin Clinical Trialsmentioning
confidence: 99%